Thrombosis of the inferior vena cava and acute kidney injury in dengue shock syndrome: A rare case with unique nursing challenges - Prabowo, Nurhasan Agung; Sari, Yulia; Putri, Desy Puspa; Habibah, Sopia Nur; Rachmah, Azkia; Hartono, Hartono (Jurnal Keperawatan Padjadjaran, 2024)
Background: Dengue Shock Syndrome (DSS) is a severe complication of dengue fever that can lead to life-threatening conditions such as thrombosis and acute kidney injury (AKI). These rare complications highlight the importance of early recognition and multidisciplinary management to improve clinical outcomes. Purpose: This case study aims to report and discuss the clinical management and outcomes of a patient with DSS complicated by inferior vena cava thrombosis and AKI, focusing on nursing interventions and therapeutic strategies. Methods: This manuscript reports a case by utilizing the patient’s baseline data, clinical progression, and treatment outcomes. A middle-aged male patient presented to the emergency department with high fever, shock, and signs of plasma leakage. Laboratory and imaging findings confirmed DSS with AKI and inferior vena cava thrombosis. The patient received fluid resuscitation, inotropic support, anticoagulation therapy, and multidisciplinary care, including close nursing monitoring. Results: After seven days of hospitalization, the patient showed significant improvement, with resolution of shock, normalization of platelet count, and recovery of renal function. Comprehensive nursing care, including vital sign monitoring, medication management, and patient education, played a pivotal role in the recovery process. At a follow-up visit on day 12, the patient demonstrated full recovery with no complications. Conclusions: This case highlights the importance of early diagnosis and a multidisciplinary approach, including cautious anticoagulation therapy, to effectively manage DSS with thrombosis and AKI. Integrating nursing interventions and strict monitoring were crucial to achieving positive clinical outcomes. This report provides valuable insights into managing similar cases in endemic areas.